2018
DOI: 10.7567/jjap.57.07ld06
|View full text |Cite
|
Sign up to set email alerts
|

Propagation characteristics of longitudinal-type leaky surface acoustic wave on layered structure consisting of ScxAl1−xN film/LiNbO3substrate

Abstract: A longitudinal-type leaky surface acoustic wave (LLSAW) has a high phase velocity. Therefore, LLSAW devices are suitable for applications to high-frequency filters. However, the attenuation of LLSAWs is higher than that of other SAW modes. This higher attenuation of LLSAWs, which causes a low Q factor, can be reduced by growing a higher-velocity film on a piezoelectric substrate. On the other hand, K2 in the layered structure decreases because of the small piezoelectricity in high-velocity films. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…The c-axis direction is controlled by rotating the Euler angles. 26,27) Therefore, the excitation SAW modes and their propagation characteristics for different Euler angles (0°, θ, ψ) were analyzed. Furthermore, the influences of the Euler angles and the film thickness normalized by the wavelength (h ScAlN /λ) of the ScAlN thin films on design and application of high-frequency and wideband SAW devices.…”
Section: Introductionmentioning
confidence: 99%
“…The c-axis direction is controlled by rotating the Euler angles. 26,27) Therefore, the excitation SAW modes and their propagation characteristics for different Euler angles (0°, θ, ψ) were analyzed. Furthermore, the influences of the Euler angles and the film thickness normalized by the wavelength (h ScAlN /λ) of the ScAlN thin films on design and application of high-frequency and wideband SAW devices.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the frequency of SAW resonators, the utilization of longitudinal leaky SAWs (LLSAWs) with a phase velocity of 1.5-2 times that of conventional LSAWs has been studied. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, our research group has reported that, by bonding a piezoelectric LiTaO 3 (LT) or LiNbO 3 (LN) thin plate, having a thickness of less than one wavelength (1 λ), to a high-phase velocity support substrate such as quartz (Qz), LLSAWs with a large Q and K 2 of 2-3 times of that of a single LT or LN can be produced owing to a strong concentration of particle displacement in the thin plate. 9,[12][13][14][15] Several research groups, including ours, have reported that bonded structures comprising an LT or LN thin plate and Qz support substrate exhibit high-performance properties with wider FBW, higher Q factor, and better temperature coefficient of frequency than those in the single substrate for LSAWs.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that attenuation in LLSAWs can be reduced by loading high-velocity AlN or ScAlN polycrystalline films on piezoelectric substrates. [3][4][5][6][7] However, the K 2 in these layered structures was significantly decreased. On the other hand, we reported that LSAW and LLSAW devices with piezoelectric thin plates bonded to high-velocity substrates (quartz and sapphire) have a high K 2 and high Q factor.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several researchers have studied the characteristics of ScAlN film bulk acoustic wave (BAW) resonators [14][15][16][17][18][19] and ScAlN film SAW resonators. 6,20,21) The electromechanical coupling coefficient of an AlN-based film BAW resonator is dramatically increased by heavily doping the AlN film with Sc. 19) SAW resonators consisting of a ScAlN layer/SiC substrate reported by Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation